2014
DOI: 10.1176/appi.ps.201300253
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Management for Children and Adolescents: Assessing the Evidence

Abstract: Behavioral management services should be considered for inclusion in covered plans. Further research addressing the mechanisms of effect and specific populations, particularly at the school level, will assist in bolstering the evidence base for this important category of clinical intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Current mental health promotion strategies employed in secondary schools have not been shown to reduce the rates of depression or anxiety in adolescence nor identify prodromal or acute FEP. 45,199,200,202,[213][214][215][216][217]220 These strategies have not led to interventions that assist young people with mental ill health to finish school. Not completing secondary school can limit employment options, lead to severe levels of disadvantage and increased burden on welfare and healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current mental health promotion strategies employed in secondary schools have not been shown to reduce the rates of depression or anxiety in adolescence nor identify prodromal or acute FEP. 45,199,200,202,[213][214][215][216][217]220 These strategies have not led to interventions that assist young people with mental ill health to finish school. Not completing secondary school can limit employment options, lead to severe levels of disadvantage and increased burden on welfare and healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…200,220 The results of these studies showed that these interventions are not effective at improving or preventing anxiety or depression. 45,200,202,[213][214][215][216][217]220 An Australian randomized controlled study implemented by Beyondblue aimed to address the prevention of depression in secondary school students. 218 Twenty-five pairs of Australian secondary schools were matched on socioeconomic status and randomly assigned to either an intervention or a comparison group (n = 5634, Year 8 students).…”
Section: Current Mental Health Strategies Employed In Secondary Schoolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Universal approaches have been studied for a broad range of presentations, including behavioural management, risky behaviours, and mood and anxiety disorders. 68 …”
Section: Mental Health Prevention: a Multitiered Approachmentioning
confidence: 99%
“…Many prevention and treatment approaches that have demonstrated effectiveness in promoting adolescent mental and behavioral health are family-centered 1. The effectiveness of family-centered programs suggests the importance of family factors in contributing to and protecting against adolescent behavioral and emotional problems.…”
Section: Introductionmentioning
confidence: 99%